Microaccelerometer on Surface Acoustic Waves with a Ring Resonator on Anisotropic Material - Dmitry P. Lukyanov; Alexander M. Boronakhin; Sergey Yu. Shevchenko; Mariya A. Khivrich; Temurmalik A. Amirov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Diagnostic systems are designed to monitor the condition of operational components (for example, on the railway). It is imperative that micro-electromechanical systems (MEMS) equipped with acceleration sensors (accelerometers) be used as part of measuring diagnostic systems. It is known that accelerometers are operated under increased vibration and repeated shock loads. This imposes a limitation both on the accelerometer design and the properties of materials from which these devices are produced.Aim. To develop a micromechanical accelerometer (MMA) for surface acoustic waves (SAW), capable of measuring shock effects.Materials and methods. The theoretical part of the study was carried out using the mathematical theory of differential equations, theoretical mechanics, finite element analysis and elements of SAW theory. In the course of the work, the following methods of mathematical processing were applied: MATLAB, Mathcad, Maple, COMSOL Multiphysics, OOFELIE: Multiphysics, Bluehill3 software, CorelDRAW. Experimental studies were also conducted using the INSTRON 5985 floor automated test system.Results. An original design of MMA on a SAW capable of measuring shock effects in hundreds of g was proposed. A sensing element (SE) of the sensor was developed. An analysis of the plate materials for their use as part of the SAW-based MMA design showed that SE from the quartz ST-cut material has a wider range of measured accelerations and a higher sensitivity threshold than SE from the YX-128˚ cut-off lithium niobate material. Requirements were developed to increase the SE sensitivity threshold. Design requirements were developed, and an interdigital transducer (IDT) topology in the form of a ring resonator was proposed. The following output characteristics were assessed: sensitivity threshold, dynamic range and scale factor. In addition, a procedure was developed for calculating MMA on a SAW with a ring resonator on an anisotropic material. It was found that the developed SE is characterized by a high sensitivity threshold, a wide dynamic range and a low transverse sensitivity.Conclusion. The technique proposed for designing a sensing element for use in solid-state linear acceleration sensors facilitates, depending on technical requirements, selection of construction materials and sensor design. Due to the originality of the design and engineering solutions, the proposed accelerometer allows measurements to be carried out across a wide range of impact loads.